P249 365 DAYS OF NOT ONLY COVID–19. DATA COHORT FROM THE HEART FAILURE OUTPATIENT'S AMBULATORY UNITE –IVREA HOSPITAL. (18th May 2022) - Troiano, F; Fornengo, C; Almohani, A; Grosso Marra, W
Abstract: The years 2020 and 2021 will always be remembered as the years of the SARS–Cov–2 pandemic, affecting and utilizing much of the world's economic and humanitarian resources, especially in the health sector. At the start of 2020, Ivrea Hospital opened a new heart failure ambulatory unit. This unit was quickly set side to face the emerging health emergency of SARS–Cov–2. It was only in September 2020, with the reorganization of the hospital services, that the new unit could once again be used for outpatient visits. For this reason, this paper only covers the analysis of patients in our service from September 2020 to September 2021. During this time, 143 patients with heart failure have been evaluated as outpatients, most of whom were men (114 men, 29 females), with an average age of 70 years. The main reason for admission was ischemic cardiomyopathy (54%), although in 28% of cases the etiology was instead defined as idiopathic, on the basis of the diagnostic investigation performed. All patients had heart failure phenotype with reduced ejection fraction according to the latest ESC guidelines, with an average value of left ventricular ejection fraction of 38%. 24% of the patients received therapy with Sacubitril/Valsartan either introduced or optimized during outpatient's follow–up. The remaining 44% of the patients (64) had sudden cardiac death prevention devices (ICD) implanted, 43% of whom had cardiac resynchronisation (Biventricular ICD– CRT–D). During the follow–up period, 10 patients died, of whom, one patient due to complications of Sars–Cov2 interstitial pneumonia, one patient due to early complications after LVAD implantation and the remaining patient due to progression of their heart failure condition, in which LVAD/transplantation was previously excluded. One patient underwent a successful heart transplant. The data presented reflect the reality of a medium sized center in the province of Turin and is aligned with what is reported by the scientific literature.